The Influence of Social Media Influencers on Trust and Digital Consumers’ Purchase Decisions - Iffah, Nida Ul (Proceedings Series on Social Sciences & Humanities, 2025)
Digital transformation has revolutionized marketing strategies by shifting focus from conventional media toward digital platforms, especially social media. In this context, Influencer Marketing has emerged as an increasingly popular and effective approach for reaching audiences in a personal, relatable manner. Influencers—with large followings and high engagement—can shape public opinion and affect consumers' purchase decisions. This study aims to analyze the effect of influencer recommendations on purchase decisions and to evaluate consumers’ trust in promotional content produced by influencers. Employing a descriptive qualitative framework supplemented with quantitative data from an online questionnaire distributed to active social media users, the research revealed that the average influence score of influencer recommendations is 3.0 out of 5, while trust in influencer reviews averages 3.2 out of 5. These findings indicate that trust is a critical component in digital branding strategies, even when consumers remain selective and skeptical of content authenticity. Therefore, businesses must prioritize transparency and authenticity in influencer collaborations to enhance credibility and campaign effectiveness.